THE OMKARESHWARA TEMPLE: A SYMBOL OF COMMUNAL HARMONY AND SPIRITUAL DEVOTION IN COORG, KARNATAKA - Rev. Sr Alex Rani SJT (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Located in the heart of Coorg, Karnataka, the Omkareshwara Temple is a revered sacred site that embodies the rich cultural and spiritual heritage of the region. Dedicated to Lord Shiva, this 19th-century temple is a masterpiece of Islamic-style architecture, reflecting the syncretic traditions of the region. Through a nuanced analysis of the temple's architecture, rituals, and festivals, this research highlights the importance of preserving India's sacred heritage sites and promoting interfaith understanding and dialogue.This study delves into the history, architecture, and cultural significance of the Omkareshwara Temple, exploring its role as a symbol of communal harmony and spiritual devotion. Through a nuanced analysis of the temple's architecture, rituals, and festivals, this research highlights the importance of preserving India's sacred heritage sites and promoting interfaith understanding and dialogue.